De nuevo sobre la tésera Froehner (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The enlargement of the Celtiberian corpus has raised two objections against the traditional interpretation of Froehner’s tessera as an unilateral hospitium agreement regarding an individual coming from Contrebia Belaisca: on one hand, the origo mention has turned to be an exceptional  fact in Celtiberian epigraphy, attested only in one document –the Ibiza in- scription– and expressed in it through a gentile adjective instead of the toponym in ablative used in Froehner’s tessera (belikios versus kontebiaz belaiskaz); on the other hand, it happens something similar with hospitium unilateral agreements regarding an individual which are now a minority compared to those regarding a city or to bilateral ones: furthermore some of the last show interesting connections with Froehner’s tessera (for instance lazuro kosokum tarmestutez kar). The additional fact that a careful examination of the inscription shows two different hands writing the text (one for lubos alizokum aualo ke., the other for kontebiaz belaiskaz) moves to considere this document in an alternative way: as a bilateral agreement between Lubos from the Alisoci, the son of Avalo, and the city of Contrebia  Belaisca.